Kualitas Hidup Balita Stunted - Sri Hendrawati; Henny Suzana Mediani; Nada Shofi Salsabila (Universitas Malahayati Lampung, 2023)
ABSTRACT The incidence of stunting in Indonesia is now a major nutritional problem. Stunted state is the beginning of the occurrence of stunting in children and allows influence also on the quality of life of children. This study aimed to see a picture of the quality of life of stunted toddlers. This research design used quantitative descriptive research. The population to be studied were all children with stunting aged 2-5 years in the Banjaran Community Health Center working area, Bandung Regency. The sampling technique used in this study was total sampling with a sample of 151 children. Assessment of the quality of life of stunted children was measured using the PedsQLTM 4.0 Generic Core Scales Proxy Parent Report instrument from Varni. Analysis of the data used in this study was univariate analysis using the mean value. The results of this study indicated that stunted children aged 2-5 years have a good quality of life of 59.6% and bad as much as 40.4%. The mean value of the whole individual respondent was 83.2 that was still poor value will be at risk of causing stunted children to become stunted. The conclusion from this study was that the average quality of life of stunted toddlers was good, but the quality of life of stunted toddlers was not necessarily good either. It was expected that parents and health workers can maintain the quality of life of these toddlers who were already good to stay good or even improve by making efforts to prevent stunting. Keywords: Quality of Life, Stunted, Toddler. ABSTRAK Kejadian stunting di Indonesia kini menjadi permasalahan gizi utama. Keadaan stunted merupakan awal dari kejadian stunting pada anak dan memungkinkan berpengaruh juga terhadap kualitas hidup anak. Penelitian ini bertujuan untuk melihat gambaran kualitas hidup balita yang mengalami stunted. Rancangan penelitian ini menggunakan penelitian deskriptif kuantitatif. Populasi yang akan diteliti adalah semua anak penderita stunting usia 2-5 tahun di Wilayah Kerja Puskesmas Banjaran Kota Kabupaten Bandung. Teknik sampling yang digunakan dalam penelitian ini adalah total sampling dengan jumlah sampel 151 anak. Penilaian kualitas hidup anak stunted diukur menggunakan instrumen PedsQLTM 4.0 Generic Core Scales Proxy Parent Report dari Varni. Analisis data yang digunakan dalam penelitian ini adalah analisis univariat dengan menggunakan nilai mean. Hasil penelitian ini menunjukkan bahwa balita stunted usia 2-5 tahun memiliki kualitas hidup baik sebanyak 59,6% dan buruk sebanyak 40,4%. Nilai mean dari keseluruhan individu responden adalah 83,2 nilai yang masih buruk ini akan berisiko menyebabkan balita stunted menjadi stunting. Simpulan dari penelitian ini adalah rata-rata kualitas hidup balita stunted baik, namun kualitas hidup balita stunting belum tentu baik juga. Diharapkan orang tua dan tenaga kesehatan dapat menjaga kualitas hidup balita yang sudah baik ini agar tetap baik atau bahkan meningkat dengan melakukan upaya penyuluhan untuk pencegahan stunting. Kata Kunci: Balita, Kualitas Hidup, Stunted.